Social Enterprise as a Catalyst for Progress Toward the Sustainable Development Goals : A Multi-Case Study - Kim, Eundeok; Fairley, Andrew (International Journal of Costume and Fashion, 2024)
Social enterprises (SEs) have recently received increasing attention from academics due to their potential link to sustainable development (SD). However, empirical research on their sustainable business models and strategies is lacking, particularly those of small- and medium-sized enterprises. Therefore, this study aims, first, to empirically examine the environmental and social sustainability practices of the selected small-sized SEs; second, to explore their keys to success and opportunities and threats; and third, to examine the contributions of the sustainability practices to the UN Sustainable Development Goals (SDGs). Their sustainable business models are analyzed within the framework of circular economy (CE). A qualitative method was adopted employing in-depth interview techniques and document analysis. The findings revealed that their environmental sustainability practices were embedded into their entire value chains, employing CE’s R principles. For their social sustainability practices, they practice fair trade, promote gender equity, develop the local economy, hire disadvantaged people, and empower their employees. This study extends the literature on how a SE creates value in its alignment to a CE and makes positive social and environmental impacts on the global society. It also offers scholars and practitioners with valuable insights on how a SE contributes to the UN SDGs. KCI Citation Count: 0